Climatic Factors Influencing Aleppo Pine Sap Flow in Orographic Valleys Under Two Contrasting Mediterranean Climates - Ana M. Sabater; José Antonio Valiente; Juan Bellot; Alberto Vilagrosa (Hydrology)
Global climate change projections highlight the Mediterranean Basin as one of the most susceptible areas to the effects of intense and prolonged droughts, as well as increasing air temperatures. Accordingly, the productivity and survival of forests in this area will depend on their ability to resist and adapt to increasingly drier conditions. Different climatic conditions across the Mediterranean Basin could drive differences in forest functioning, requiring trees to acclimate to them. Sea breeze dynamics along orographic valleys can also influence climatic conditions, accentuating differences between inland and coastal forests. However, there is limited information on whether the climatic factors regulating tree transpiration in Aleppo pine forest in orographic valleys vary according to climate. This study aims to identify and compare the climatic factors that regulate tree transpiration along a gradient and determine the thresholds at which these factors affect transpiration rates. This study was carried out by means of sap flow gauges, since this technique is a key feature for quantifying and understanding tree transpiration. It was conducted in two Aleppo pine dry sub-humid forests (inland and coastal, 750 and 675 trees ha−1, respectively) and in two pine semi-arid forests (inland and coastal, 600 and 400 trees ha−1, respectively) in the western Mediterranean basin during January–November of 2021. No significant rainfall events or droughts were recorded during the period of study, indicating a standard climatic condition in these areas. The main findings demonstrated that the variability in sap flow could be attributed to the interaction between soil water content and vapour pressure deficit in all the forests studied. However, the highest threshold values of these climatic factors in relation to the increase or decrease in maximum sap flow (i.e., less sensitivity) were exhibited in semi-arid forests, highlighting the adaptability of Aleppo pine to more limiting climatic conditions. These findings are relevant for the consequences of the predicted increase in harsh climatic conditions and the balance among vapour pressure deficit, temperature and soil water availability. Future research will be essential to confirm forest acclimatisation in the transitional dry to semi-arid forest ecosystems predicted by global climate change projections, given their potential to strongly alter ecosystem function and water cycles.